Selección y manejo del potencial donante de órganos - Rojas B., José Luis; Cortés S. , Esteban (Revista Hospital Clínico Universidad de Chile, 2007)
In Chile, an average of 135 effective donors in brain death for organs transplants are generated by year ; which it means over 330 solid organs transplants annually. This number corresponds at the 85% of total transplants made in Chile, whereas 15% rest is from living donor. Of all the stages involved in donor generation, two basic pillars exist: Detection/Selection to accurate an increase in the global number of donors and the Donor Management, directly related with quality an security of transplanted organs. Brain Death it associates to haemodynamic, metabolic and internal equilibrium changes what means directly in hypoperfusion of transplanted organs. Considering also in brain death as in donors generation steps, all the health professionals should be involved, this review present recommendations to equal and optimize to the maximum the optimal care of the potential organ donor.